2019
DOI: 10.1074/mcp.ra117.000459
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Features of Proteins Depicting the Chicken Amniotic Fluid

Abstract: SUMMARYIn many amniotes, the amniotic fluid is depicted as a dynamic milieu that participates in the protection of the embryo (cushioning, hydration, and immunity). However, in birds, the protein profile of the amniotic fluid remains unexplored, even though its proteomic signature is predicted to differ compared to human's. In fact, unlike humans, chicken amniotic fluid does not collect excretory products and its protein composition strikingly changes at mid-development due to the massive inflow of egg white p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
0
32
0
1
Order By: Relevance
“…Direct transfer of gut proteins to the allantoic sac is also likely to occur [83]. EW anti- Listeria monocytogenes and anti- Streptococcus uberis activities are maintained during embryonic development up to ED12 [84], and EW antibacterial proteins have been shown to be active even after their transfer into the amniotic sac [20]. …”
Section: Egg Basic Structures and Innate Immunitymentioning
confidence: 99%
See 3 more Smart Citations
“…Direct transfer of gut proteins to the allantoic sac is also likely to occur [83]. EW anti- Listeria monocytogenes and anti- Streptococcus uberis activities are maintained during embryonic development up to ED12 [84], and EW antibacterial proteins have been shown to be active even after their transfer into the amniotic sac [20]. …”
Section: Egg Basic Structures and Innate Immunitymentioning
confidence: 99%
“…Following EW transfer, its antibacterial proteins may also contribute to protect the embryo before and after hatching, like the vernix caseosa in humans [125]. Interestingly, several proteins recovered in the AmF prior and after EW transfer are uniquely found in birds (OVAL and its related proteins OVAX and OVAY, and also AvBD11) or oviparous species (vitellogenin [VTG]1, VTG2, and riboflavin-binding protein [RBP]) [20]. …”
Section: Embryonic Structures and Their Role In Egg Defensementioning
confidence: 99%
See 2 more Smart Citations
“…protective, nutritive, and immune functions, but the overall protein composition is complex and poorly understood. Da Silva et al (31) use LC-MS/MS to identify doz-ens of proteins present in the chicken amniotic fluid proteome before the influx of massive amounts of egg white proteins. Importantly, they found that 48 of these were common to both chicken and humans amniotic fluids defining a target set of high-quality proteins with potentially conserved function in developing egg and fetus.…”
mentioning
confidence: 99%